Creating a Website to Manage the Stores of the Dialysis Center -Zliten - Ermis, Marah Ali; Hawedi, Hadya S.; Alter, Rawnaq Mustafaa; Alrsawi, Sumaya Omran (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The concepts of analysis and design of automated systems and concepts of databases are among the most important contemporary methods of data storage and information retrieval. In this research, concepts of analysis and design of automated systems and concepts of databases were applied using special tools to implement a website to manage the stores of the dialysis center in Zliten. Where this site was created due to the problems resulting from the manual system, the main objective of creating this site was to convert manual operations into automated operations carried out by computer, and with the help of God, manual operations were converted into automated operations using one of the languages. On this site, we designed the interfaces using the php language in order to facilitate the user's flexible handling of the site in entering data and outputting reports at any time and managing the warehouse operations easily and, smoothly. The study recommends adding barcode technology in the process of storing items in the database, and adding an integrated protection system to ensure the continuity of the system's work with high efficiency.
Keywords: Website; Dialysis Center; php; Zliten